TAS’IR PERSPEKTIF FIQH KLASIK DAN KONTEMPORER SERTA RELEVANSINYA DALAM KEBIJAKAN EKONOMI SYARIAH NEGARA - Yuzril Mahendra; Muhamad Zen (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2025)
This article aims to understand the differences between classical and contemporary Islamic jurisprudence (fiqh) views on the phenomenon of pricing and the arguments for the rejection and permissibility of price fixing. It also aims to explain the intervention of the Indonesian government in pricing, particularly fuel, food, basic necessities, and pricing by LKS banking and non-banking Muamalah authorities. The method in this research uses a descriptive qualitative approach with a literature review approach through a process of critical analysis and synthesis of books, journals, and information from the internet. In the context of pricing, the Indonesian government aims to prevent ihtikar practices, fraud, price stability, and public welfare. LKS banking and non-banking Muamalah conduct price fixing to ensure transactions run systematically, fairly, transparently, and protect consumers from products containing gharar. According to classical Islamic jurisprudence scholars, there are two views: prohibiting and permitting. Meanwhile, according to modern Islamic jurisprudence scholars such as Wahbah az-Zuhaili and Quraish Shihab, the government may exercise its authority to establish regulations regarding pricing. This is permissible for two reasons: the occurrence of ihtikar (scams) and sales practices that take profits exceeding 30% of the original price.